Knowledge sharing, knowledge seeking, and emotions: A longitudinal study of hospital restructuring decision making. (25th October 2022) - Chan, Yolande E.; Krishnamurthy, Rashmi; Mann, Janelle; Sabherwal, Rajiv
Abstract: Prior research examines factors that enable or hinder knowledge sharing and knowledge seeking in groups. However, individuals also share and seek knowledge outside group meetings, especially if the group is making strategic decisions over time. Therefore, this study examines how, during a longitudinal strategic decision‐making process, the emotions of group members and knowledge sharing within the group affect their knowledge‐sharing intentions and knowledge‐seeking behaviors beyond the group. We focus on a single organization, a hospital, whose board created a citizen advisory panel (CAP) of 28 individuals to gather community input on the restructuring of the hospital's activities to contain costs. The group met in five all‐day sessions to provide their input. We surveyed each member before the CAP process and after each CAP session. The resulting longitudinal data were analyzed using panel‐data techniques, with the findings being complemented by qualitative insights. The results indicate, somewhat surprisingly, that both positive and negative emotions (specifically enthusiasm and anxiety) positively affect both knowledge‐sharing intentions and knowledge sharing within groups in strategic decision‐making contexts. We also find that enthusiasm, anxiety, and perceived relative knowledge within groups positively affect subsequent knowledge‐seeking behaviors. Our findings contribute to the literature on knowledge management and organizational decision making. The study provides insights into how, in groups making strategic decisions over time, emotions as well as knowledge sharing within groups affect knowledge‐related intentions and behaviors beyond the groups. The study also adds to the theory of planned behavior to highlight the role of emotions in influencing intentions and behaviors.